Effect of Virtual Reality Technology on the Accomplishment of the Natural Self-Existing In Virtual Interior Space - Ibrahim Jawad Alyousif; Zahra Mohamed Mosa (Iraqi Journal of Architecture and Planning, 2018)
due to the major technological development happened in the last 20 years, technology had great role in changing the architectural constants and classifying its priorities. Many studies focused on technology notion and its application in architecture. But they did not focus on the rule of technology to realize Human reliance on internal and external spaces in which the people spend most of their time in.The information technology with its developments has great impact on actions & behaviors of human beings. Here the research idea in “Lack of sufficient scientific knowledge about the impact of technology of virtual reality to achieve the existential nature of the personality in virtual space. The search aimed to discuss "Clarifying the role of virtual reality technology to establish an internal virtual theoretical framework of space which seeks to achieve human existential lost in realistic space achieving the goal required having Comprehensive theoretical framework .This theoretical framework as a first stage of theoretical framework .The second stage of tries to clarify the main levels of the practical study to clarify truth fullness of indicators achieved through out:selecting items of theoretical framework. The final conclusions of the research which include theoretical framework conclusions, application results conclusions.